The Second International Conference on the Roles of the Humanities and Social Sciences in Engineering (ICoHSE2010) - Anon (Universiti Malaysia Perlis (UniMAP), 2011)
The Second International Conference on the Roles of the Humanities and Social Sciences in Engineering (ICoHSE2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 13rd November 2010 at Bayview Beach Resort, Penang, Malaysia.